Development of Jazz Music Ensemble Curriculum Based on Albert Bandura’s Observational Learning Concept, Case Study Xinghai Conservatory of Music - Haiming, Zhu; Phokha, Pramote; Chiangthong , Nut (Journal of Ecohumanism, 2025)
This study aims to enhance jazz ensemble skills among professional music students at the Xinghai Conservatory of Music by developing a Jazz Music Ensemble Curriculum rooted in Albert Bandura’s Observational Learning theory. The curriculum focuses on improving students' improvisational skills and musical literacy through a structured, socially interactive learning process. The study employs a mixed-methods approach, using qualitative interviews with jazz education experts at the conservatory for insights into best practices and quantitative analysis to assess the impact on 20 jazz music majors from the 2022 cohort. Findings highlight that Bandura’s Observational Learning, a key aspect of social learning theory, differs from traditional conditioning by prioritizing learning through observation, imitation, and modeling rather than direct experience alone. In a jazz ensemble context, this approach enriches music education by fostering social learning, cognitive engagement, and emotional expression. By selecting skilled role models, encouraging active observation, and creating a supportive environment, educators can effectively boost students' technical skills, self-confidence, and enjoyment of jazz. This method not only prepares students artistically and technically but also supports their growth as expressive, collaborative, and reflective musicians, making them more adaptable and engaged in the jazz genre.